2019
DOI: 10.2131/jts.44.459
|View full text |Cite
|
Sign up to set email alerts
|

The effects on the endocrine system under hepatotoxicity induction by phenobarbital and di(2-ethylhexyl)phthalate in intact juvenile male rats

Abstract: Phenobarbital (PB) and Di (2-ethylhexyl) phthalate (DEHP), an anti-epileptic drug and a plasticizer used in flexible polyvinylchloride formulations, respectively, are well-known typical hepatotoxicants. This study investigated the effects of PB (100 mg/kg/day) or DEHP (500 mg/kg/day) on the endocrine system in intact juvenile/peripubertal male rats exposed for 31 days beginning on postnatal day 23. Slight hormone level changes, histopathological changes in thyroid gland or induction of UDPglucuronosyltransfera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…Mitochondrial toxicity and oxidative stress is involved in the hepatotoxicity induced by phenobarbital [38,39]. Laboratory animal studies have reported the hepatotoxicity of high dose phenobarbital in juvenile male rats [40]. The hepatoxicity is suggested to be related to defect in phenobarbital detoxi cation and hypersensitivity [28].…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial toxicity and oxidative stress is involved in the hepatotoxicity induced by phenobarbital [38,39]. Laboratory animal studies have reported the hepatotoxicity of high dose phenobarbital in juvenile male rats [40]. The hepatoxicity is suggested to be related to defect in phenobarbital detoxi cation and hypersensitivity [28].…”
Section: Discussionmentioning
confidence: 99%
“…Nonparametric tests (e.g., Kruskal-Wallis or Mann-Whitney tests [34]) are commonly used for ordinal response data but tied data are considered only an approximation and confidence intervals are hard to obtain or to interpret. New proposals for related trend tests, e.g., Altunkaynak and Gamgam [3] suffer from the same issues.…”
Section: A Nonparametric Approach Based On Relative Effect Sizementioning
confidence: 99%
“…1,5 For example, phenobarbital (PB), a common drug, is a well-known liver-mediated thyroid toxicant in rodents. 6,7…”
Section: Introductionmentioning
confidence: 99%
“…1,5 For example, phenobarbital (PB), a common drug, is a well-known liver-mediated thyroid toxicant in rodents. 6,7 Both MIEs (direct or indirect) trigger a decrease of circulating thyroid hormone concentrations, which lead to an activation of the hypothalamus-pituitary axis via a negative feedback and then a stimulation of thyroid gland by thyroid stimulating hormone. If this stimulation is prolonged, histomorphological changes like follicular cell hypertrophy, hyperplasia, and potentially neoplasia could be observed.…”
Section: Introductionmentioning
confidence: 99%